Cytochrome P450 2B6 and 2C9 genotype polymorphism – a possible cause of prasugrel low responsiveness - Franken, Cora C.; Kaiser, Andreas F. C.; Krüger, Jan C.; Overbeck, Kristina; Mügge, Andreas; Neubauer, Horst (Thrombosis and Haemostasis, 2013)
The cytochrome P450 (CYP) isoenzymes are essential for the metabolic activation of the prodrug prasugrel. Little is known about the impact of polymorphism of these isoenzymes on the prevalence of prasugrel low responsiveness (PLR) in patients with coronary artery disease. We investigated the frequency of PLR and the question whether PLR is associated with decreased/non-function polymorphisms of the CYP isoenzymes (2C9*2, 2C9*3, 2C19*2, 2C19*3, and 2B6*6). Our study included 355 patients who underwent percutaneous coronary stenting. The patients were initially treated with either prasugrel (n=90; 60/10 mg: loading/daily maintenance dose) or 600/75 mg clopidogrel hydrogensulfate (n=265) in combination with 500/100 mg acetylsalicylic acid (ASA). Platelet function was tested by impedance aggregometry 48 hours after taking the loading dose. Prasugrel achieved on the average significantly higher levels of platelet inhibition as compared to clopidogrel (mean 27.3 U vs 41.2 U). The frequencies of low response for prasugrel, clopidogrel and ASA were 9.8%, 35.1% and 14.9%, respectively. We identified only body mass index to be associated with PLR. PLR was not caused by a loss of ADP P2Y12-receptor function. Half of the patients with PLR were carriers of the reducedfunction allele CYP2B6*6, and 41.7% had the genetic variant CYP2C9*2. The allele CYP2C9*3 was detected in three patients with PLR (25%) and two patients with PLR (16.7%) carried the gene variant CYP2C19*2. In conclusion, the rate of low responders was significantly lower among patients treated with prasugrel than with clopidogrel. PLR are more often carriers of CYP2C9*2 (50% in PLR) than when compared to the prevalence described in literature. Also, there is a trend to an increased frequency of CYP2B6*6 in PLR. In conclusion, CYP2B6 and CYP2C9 polymorphisms seem to be associated with prasugrel low-response.
Keywords: Prasugrel; clopidogrel; low responder; platelet aggregation; cytochrome P450